Changes in aerosol particle composition during sea fog formation events in the sea ice regions of the Arctic Ocean. (1st March 2022) - Zhao, Shuhui; Yan, Jinpei; Lin, Qi; Yao, Lei; Park, Keyhong; Jung, Jinyoung; Chen, Liqi; Xu, Suqing; Sun, Meiping; Wang, Shanshan; Yang, Hang; Shi, Jun; et al.
Abstract: Water soluble ions (WSIs) of aerosol particles is one of the important parameters to study the aerosol-fog interactions. To study the changes of aerosol WSIs during sea fog events, hourly real-time measurements of WSIs (Na +, K +, Mg 2+, Ca 2+, MSA −, Cl −, NO3 −, and SO4 2− ) in total suspended aerosol particles (TSP) were conducted in the atmosphere over Arctic Ocean ice floe regions from August 1 to 12, 2017, when the sea fog events were frequently observed. There were significant differences in Na +, Cl −, Mg 2+, methanesulfonic acid (MSA − ), sea salt sulfate (ss-SO4 2 ) and non-sea salt sulfate (nss-SO4 2- ) ions during sea fog events vs. non-sea fog periods. The mass concentrations of sea salt ions, such as Na +, Mg 2+, Cl − and ss-SO4 2-, clearly increased before the occurrence of sea fog and then decreased substantially with the formation of sea fog; however, nss-SO4 2- levels did not decrease but remained high during the sea fog processes. These results suggest that sea salt aerosol particles were more likely to serve as condensation nuclei for fog and could be more effectively removed by sea fog than nss-SO4 2- particles. MSA − only combined with sea salt particles, which were likely to serve as condensation nuclei and be removed by sea fog. Condensation may be the primary factor leading to the reduction of sea salt ions during the sea fog periods, while other factors like the presence of dense sea ice and long-range transport input may also affect the decreasing rate. Highlights: Hourly real-time measurements of aerosol compositions were conducted during sea fog events in the Arctic Ocean. Sea salt aerosol concentrations increased before sea fog formed, but decreased dramatically when sea fog formation began. Non-sea-salt sulfate (nss-SO4 2- ) concentrations remained consistently high during sea fog formation processes. Condensation may be the primary factor leading to the reduction of sea salt ions during the sea fog periods.